Pengaruh Return on Assets dan Kebijakan Hutang Terhadap Kebijakan Dividen Pada Perusahaan Perbankan Terdaftar di BEI Periode 2016-2020 - Muhammad Alfero; Harun Blongkod; Siti Paratiwi Husain (Jambura Accounting Review, 2022)
The research aims to find outthe effect of Return On Assets (ROA) and debt policy on the dividend policy in the banking firms listed in Indonesia Stock Exchange during period of 2016-2020. The research applies a quantitative descriptive method where the data used are secondary data obtained from firms’ financial statement. The samples in this research are 50 data from 10 banking firms listed in Indonesia Stock Exchange during 5 years. The technique of data analysis employs Multiplke Linear Regression. The research findings indicate that the Return On Assets (ROA) does not effect the dividend policy, whereas the debt policy affects the dividend policy in the banking firms listed in Indonesia Stock Exchange during period of 2016-2020. Simultaneously, the Return On Assets (ROA) and Debt Policy do not affect the dividend policy significantly.